Information sources and attitudes of Polish migrants accepting or declining vaccination in Scotland. (13th November 2019) - Gorman, D R; Bielecki, K; Willocks, L; Pollock, K; Munshaw, J; Larson, H
Abstract: Background: Poland has the lowest EU vaccine confidence scores. The Polish are the largest migrant group in Scotland (91, 000) with a high decline rate of nasal influenza vaccination. A new Polish language information leaflet in the 2018 school influenza programme saw consent form return increase but uptake remained low. We compare vaccination attitudes of accepting and declining parents. Methods: A questionnaire to 365 Polish parents after vaccination asked about the leaflet, vaccination, time in UK and included WHO Vaccine Hesitancy statements. Accepting and declining parents were compared. Results: 128 (37%) responded - 42% of vaccinating and 39% declining parents. 90% were long term UK resident, 72% speak Polish at home. Previous experience had most influence in vaccination decision-making, with social media and personal contacts in Poland and Scotland also key. Decliners were more likely to cite social media than accepters. Concerns about new vaccines, side effects and 'currently uncommon conditions' are high in the Polish community and decliners hold more negative and scientifically 'incorrect' opinions. Parents know that Polish and UK immunisation schedules differ for influenza, a condition thought less serious in Poland than UK. Conclusions: Polish norms strongly influence this migrant group. Differences in how Polish migrants who accept or decline the vaccination respond to vaccine hesitancy statements plus knowing that Polish media and the Polish community shape their views can be used by health authorities to target health messages. It is important to be aware of immunisation status and vaccination beliefs of mobile migrant groups, such as the Polish, to prevent spread of vaccine preventable diseases in Europe. Linking vaccine hesitancy statement responses and behaviour can highlight national characteristics and particular concerns of vaccine hesitant parents. This information could be used to improve vaccine uptake rates among different ethnic minorities. Key messages: Polish migrant children have low nasal influenza vaccine uptake. Vaccine hesitancy statements show decliners are particularly likely to distrust new vaccines and worry about vaccine side effects. Migrants access Polish social media and information and retain vaccination beliefs and norms post migration. Knowing this allows targeting of information campaigns to increase uptake.